Analyzing anthropogenic impact on Ibanda-Makera natural forest in Kirehe district - Kalinda, Mory Vital; Ndokoye, Pancras; Ndagijimana, Onesphole (Journal of Forests, 2023)
Human pressure from farming activities on marginal lands, and on forest reserves in particular, have resulted in the loss of the large number of hectares of natural forests. This problem also occurred on Ibanda-Makera natural forest locating in Kirehe District, Eastern Province of Rwanda. In this study, we study anthropogenic impact on Ibanda-Makera natural forest. The identification of anthropogenic activities affecting Ibanda-Makera natural forest was done; their impacts on forest was analyzed; and the level of degradation in terms of forest cover of Ibanda-Makera was determined. The study adopted both qualitative and quantitative methods to collect data from a sample of 97 individuals in the target population of 3,330 people. Data were collected using questionnaire, interview guide techniques and documentation. Through SPSS analysis, Pearson correlation between anthropogenic activities and forest degradation, the results showed that people have an understanding on factors leading to the forest degradation and that land use activities surround the Ibanda-Makera area were not in way of protecting forest as priority. Change detection from analysis of 2012, 2017 and 2022 images under supervised classification using remote sensing data of Ibanda-Makera natural forest, showed spatial variation where degradation is high between 2012 to 2017 and low between 2017 to 2022 expressing that between 2017 to 2022 under some environmental guidelines the damaged area moved to the restoration mechanisms. The recommendation to government, regular monitoring of forest boundaries to prevent potential damages that may occur on the forest and set a local system of protection.